Extreme learning machine based financial prediction - Liu, Yishan. (2012)
Stock Prediction is important for making sound investment decisions. Various machine learning approaches have been suggested for stock forecasting. However, due to the complexity and randomness of stock market, a precise prediction method remain unsolved now and highly demanded. In the Final Year Project (FYP), a new learning algorithm called Extreme Learning